THEORETICAL APPROACH OF UNIFORM FLOW VELOCITY THROUGH GROIN PILES - Hasdinar Umar (Jurnal Riset Teknologi Kelautan, 2016)
Research of uniform flow velocity through groin piles was developed on hydraulic laboratory, which differs from previous research because model of structure is groin piles. Uniform flow is influenced by two shear stress namely bottom shear stress and shear stress due to the piles of groin. Theory of uniform flow velocity is obtained by equating the shear stress due to waves and shear stress due to permeable groins. Theoretical approach verified by research in the laboratory using eight models of piles with density ranging between 18.4% - 31.4%. The verification results show that the measurement data of uniform flow velocity in the laboratory close to the results of calculations using the theory.